2015
DOI: 10.1155/2015/193049
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Three Molecular Simulation Approaches for Cyclodextrin‐Ibuprofen Complexation

Abstract: Cyclodextrins are widely used for the solubilisation of poorly soluble drugs in the formulations. However, current cyclodextrin formulation development strongly depends on trial-and-error in the laboratory, which is time-consuming and high cost. The aim of this research was to compare three modeling approaches (Docking, molecular dynamics (MD), and quantum mechanics (QM)) for cyclodextrin/drug complexation. Ibuprofen was used as a model drug. Binding free energy from three simulation methods was calculated as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 28 publications
3
19
0
Order By: Relevance
“…According to the published thermodynamic effect of complexation in the studies of CA-HPβCD (Ks = 382.7 M −1 ) [7] and CA-βCD (Ks = 339.7 M −1 ) [8], the predicted ranks 1 and 3, respectively, remain in agreement with experimental results. In the literature, good agreement of in silico predictions with experimental results was observed for Ibuprofen systems with β−, γ−, and HPβCD, where dG of binding was simulated with the MM-PBSA approach [30]. The study revealed the most energetically favored Ibuprofen-HPβCD system, the theoretical results were confirmed experimentally.…”
Section: Discussionsupporting
confidence: 58%
“…According to the published thermodynamic effect of complexation in the studies of CA-HPβCD (Ks = 382.7 M −1 ) [7] and CA-βCD (Ks = 339.7 M −1 ) [8], the predicted ranks 1 and 3, respectively, remain in agreement with experimental results. In the literature, good agreement of in silico predictions with experimental results was observed for Ibuprofen systems with β−, γ−, and HPβCD, where dG of binding was simulated with the MM-PBSA approach [30]. The study revealed the most energetically favored Ibuprofen-HPβCD system, the theoretical results were confirmed experimentally.…”
Section: Discussionsupporting
confidence: 58%
“…The output of the command and topol.top file suggested that the zero counter ion was added to the system, as previously reported. 38 Each molecular dynamic production run was carried out for 100 ns for each complex. Each recording interval was set to 100 ps for the trajectory and 1.2 ps for the energy.…”
Section: Methodsmentioning
confidence: 99%
“…A binding interaction was analyzed to show that electrostatic interactions have the largest contribution to the stability of the cucurbituril-pseudorotaxane complex (Malhis et al, 2015 ). Complex stability was analyzed for multiple systems, such as the 1:1 and 1:2 inclusion complexes formed by nor- Seco -cucurbit[10]uril and 1-adamantanmethylammonium in water (El-Barghouthi et al, 2015 ), cyclodextrin-Ibuprofen complexes (Wang R. M. et al, 2015 ), E-selectin-oligosaccharide complexes (Barra et al, 2017 ), and the naringenin-2,6-dimethyl β-cyclodextrin inclusion complex (Sangpheak et al, 2014 ). Finally, enantiomeric discrimination of chiral organic salts by chiral aza-15-crown-5 ether with C1 symmetry was reported (Kocakaya et al, 2015 ).…”
Section: Applications Of Mmpbsamentioning
confidence: 99%